ANALISIS PENGARUH PUTUSAN HAKIM KONSTITUSI TERHADAP PUTUSAN MAHKAMAH KONSTITUSI No. 90/PUU-XXI/2023 - Anwar, Khoirul (Fakultas Ilmu Sosial dan Humaniora, 2024)
The constitution states that the Indonesian state is a rule of law enforced by the government under the mandate of paragraph 4 of the preamble to the 1945 NRI constitution, which states that its duty is to protect the entire Indonesian people and the bloodshed of all. Indonesia. manifestation of the fifth commandment and